Analysis of combustion characteristics under cooled EGR in the hydrogen-fueled Wankel rotary engine. (15th January 2023) - Meng, Hao; Ji, Changwei; Shen, Jianpu; Yang, Jinxin; Xin, Gu; Chang, Ke; Wang, Shuofeng
Abstract: Hydrogen-fueled Wankel rotary engine (HWRE), as a high power density and eco-friendly internal combustion engine, has the potential to become an alternative for gasoline-fueled piston engines. Cooled EGR, as an effective means of improving engine performance, is less studied based on HWRE. However, due to the different operating way and structure, the flame development and propagation of WRE are significantly different from those of the piston engine, so may the effect of cooled EGR. Hence, the goal of present work is to analyze the effect of cooled EGR on the combustion characteristics of HWRE. This work is conducted under 1500 r/min and wide-open throttle conditions. The results show that when the ignition timing and excess air ratio are fixed at 5°CA ATDC and 1, the cooled EGR level has a significant influence on the combustion process and operating stability. In addition, when maximum brake torque CA50 is employed, within test range, whether stoichiometric or lean combustion, both the brake torque and brake thermal efficiency are monotonous to the cooled EGR level. And cooled EGR can achieve high brake thermal efficiency compared with lean combustion at the same brake torque. Compared with the hydrogen-fueled piston engine, HWRE allows for a higher cooled EGR level whether in terms of efficiency or power output considerations. In general, the cooled EGR can be used as an excellent load control means to achieve high efficiency of HWRE. Highlights: The effect of cooled EGR on combustion in hydrogen Wankel rotary engine is analyzed. Cooled EGR has significant impacts on the combustion characteristic of hydrogen WRE. Cooled EGR can be employed as an excellent means of load control of hydrogen WRE. Cooled EGR is more suitable for hydrogen WRE than the hydrogen piston engine.